PERLINDUNGAN HUKUM TERHADAP DEBITUR DALAM PINJAMAN DANA TANPA AGUNAN DIMASA PANDEMI COVID-19 - Nur Qomariyah; Anang Dony Irawan (Prodi Ilmu Hukum, Universitas Teuku Umar, 2021)
Covid-19 has greatly affected several sectors, one of which is the economy andhealth in every country, as well as the Indonesian state which has experienced atremendous impact since the beginning of the Corona Virus in early March 2020,so the government has set a policy of credit relaxation for MSME actors who haveloan funds. which makes the bank experiencing problems with bad loans or NonPerforming Loans (NPL) so that it affects the level of bank liquidity which causesbetween debtors and creditors to experience instability. 8 of 1999 concerningProtection of debtors and efforts to settle bad loans.